Scanning electron microscopic study of the in situ effect of salivary stimulation on erosion and abrasion in human and bovine enamel - Rios, Daniela; Honório, Heitor Marques; Magalhães, Ana Carolina; da Silva, Salete Moura Bonifácio [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Machado, Maria Aparecida de Andrade Moreira; Buzalaf, Marília Afonso Rabelo (FapUNIFESP (SciELO), 2008)
This in situ study investigated, using scanning electron microscopy, the effect of stimulated saliva on the enamel surface of bovine and human substrates submitted to erosion followed by brushing abrasion immediately or after one hour. During 2 experimental 7-day crossover phases, 9 previously selected volunteers wore intraoral palatal devices, with 12 enamel specimens (6 human and 6 bovine). In the first phase, the volunteers immersed the device for 5 minutes in 150 ml of a cola drink, 4 times a day (8h00, 12h00, 16h00 and 20h00). Immediately after the immersions, no treatment was performed in 4 specimens (ERO), 4 other specimens were immediately brushed (0 min) using a fluoride dentifrice and the device was replaced into the mouth. After 60 min, the other 4 specimens were brushed. In the second phase, the procedures were repeated but, after the immersions, the volunteers stimulated the salivary flow rate by chewing a sugar-free gum for 30 min. Enamel superficial alterations of all specimens were then evaluated using a scanning electron microscope. Enamel prism core dissolution was seen on the surfaces submitted to erosion, while on those submitted to erosion and to abrasion (both at 0 and 60 min) a more homogeneous enamel surface was observed, probably due to the removal of the altered superficial prism layer. For all the other variables - enamel substrate and salivary stimulation the microscopic pattern of the enamel specimens was similar.
Keywords: Dental enamel; Scanning electron microscopy; Tooth abrasion; Tooth erosion; adult; animal; beverage; carbonated beverage; cattle; chemistry; chewing gum; dental care; dental caries; drug effect; enamel; female; food; human; male; pathology; pH; physiology; saliva; scanning electron microscopy; surface property; tooth brushing; tooth disease; ultrastructure; Adult; Animals; Beverages; Carbonated Beverages; Cattle; Chewing Gum; Dental Caries; Dental Enamel; Dental Enamel Solubility; Female; Food; Humans; Hydrogen-Ion Concentration; Male; Microscopy, Electron, Scanning; Saliva; Surface Properties; Tooth Abrasion; Tooth Erosion; Tooth Remineralization; Toothbrushing; Young Adult